Phenobarbitone induced drug reaction with eosinophilia and systemic symptoms (DRESS): a case report - Natt, Navreet K.; Singh, Tarsem; Singh, Harmanjit; Sharma, Manu; Singh, Gagandeep (International Journal of Basic & Clinical Pharmacology, 2017)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a life threatening cutaneous drug reaction with visceral involvement and hematological abnormalities. Being a rare side effect, it is often under-reported and misdiagnosed. The fatal adverse drug reaction is associated most commonly with aromatic anti-epileptics phenytoin, carbamazepine and less frequently with phenobarbitone. Here, we report a case of phenobarbitone induced DRESS in a 1 year old male child. He succumbed to fulminant hepatic failure inspite of being put on steroids, hepatoprotectives, antibiotics and ventilatory support.